2024
DOI: 10.1111/bjh.19367
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide combined with cytarabine and pegfilgrastim for poorly mobilizing patients with multiple myeloma and lymphoma: A prospective multicentre study

Peipei Ye,
Yixuan Cheng,
Jiaying Lian
et al.

Abstract: SummaryA chemotherapy‐based mobilization regimen in patients who mobilize poorly, based on etoposide, cytarabine and pegfilgrastim (EAP), has recently been introduced. The aim of this prospective study was to investigate the efficacy and safety of the EAP regimen in patients with poorly mobilizing multiple myeloma (MM) or lymphoma. This single‐arm clinical trial was performed at eight public hospitals in China and was registered as a clinical trial (NCT05510089). The inclusion criteria were; (1) diagnosis of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…It has been reported that high-dose cytotoxic agents utilized in mobilization may lead to delayed engraftment following ASCT. However, in our study, the day to neutrophil engraftment post-transplantation was comparable to Ye’s EAP protocol (median: 10 vs. 10 days) ( 34 ), and consistent with other reports ( 16 , 24 , 35 ). Several studies have reported that higher number of infused CD34+ cells was associated with faster hematologic recovery ( 30 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that high-dose cytotoxic agents utilized in mobilization may lead to delayed engraftment following ASCT. However, in our study, the day to neutrophil engraftment post-transplantation was comparable to Ye’s EAP protocol (median: 10 vs. 10 days) ( 34 ), and consistent with other reports ( 16 , 24 , 35 ). Several studies have reported that higher number of infused CD34+ cells was associated with faster hematologic recovery ( 30 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…Ye et al. recently reported the outcomes of reduced dosage etoposide (75 mg/m2/day, d1-2)+cytarabine (300mg/m2 q12h, day1-2) plus pegfilgrastim in a small cohort of poorly mobilizing MM ( n =32) and lymphoma ( n =26) patients ( 34 ). Among the 26 lymphoma patients, 21(80.8%) collected adequate amount of CD34+ cells, while only 12(46.2%) achieved optimal mobilization.…”
Section: Discussionmentioning
confidence: 99%